An Empirical Analysis on Acumen of Farmer Members on Farmer Producer Companies - S. B. Ramya Lakshmi; G. Jaya; K. C. Gummagolmath (Innovations in Science and Technology Vol. 1, 2021)
The present study was conducted in the state of Maharashtra with an objective to analyze the farmers’ perceptions on Farmer Producer Companies (FPCs) in the state of Maharashtra, India. Indian farmers still face many challenges as majority of them are small and marginal farmers accounting for more than 86 per cent of the farming population. Member farmers were selected as sample respondents for the study. The results of the present study revealed that after association with producer company, there has been an improvement in the yields as stated by 96.66 per cent of the farmers under category I, 82.73 per cent of the farmers in category II and 77.50 per cent of the farmers under category III. It was also observed that there was an improvement in the quality of the produce and a majority of the farmers were happy with the price for their produce received after joining FPCs. It was also interesting to note that the problems faced by the farmers were different in all the three categories of FPCs. However, the common problem faced by the farmers in category II and III was manipulation of quotas and quality specifications by some of the companies. The SWOT analysis revealed that the major strengths identified by the farmers were more or less same in the selected FPCs like provision of inputs and production services, higher yields due to better management, minimizing the prices risk and better bargaining for small holders. The adoption of new production technology was a common weakness and pro-government policy was an important opportunity of all the producer companies as perceived by the farmers. The common threats to the producer companies of all categories include problem of sustaining long term operations, cut throat competition among companies, social and cultural constraints.